1989
DOI: 10.1017/s0022029900028776
|View full text |Cite
|
Sign up to set email alerts
|

Tryptic phosphopeptides from whole casein. II. Physicochemical properties related to the solubilization of calcium

Abstract: SUMMARY. Casein phosphopeptides (CPP) were produced by tryptic hydrolysis of sodium caseinate and further purified by precipitation and chromatography on QAE-Sephadex A-25. Their physico-chemical properties were compared with the properties of an enzymically dephosphorylated equivalent preparation (DPP). Binding of Ca 2+ to the peptides was measured using a Ca selective electrode and was found to increase with pH and to show 1/1 stoicheiometry Ca/P org in CPP at pH 6 -5 a.nd 7-6. Klotz plots indicated equivale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(63 citation statements)
references
References 8 publications
2
60
0
1
Order By: Relevance
“…Assays with Caco-2 cells have shown that the addition of certain casein phosphopeptides (CPP-Ca) at levels higher than 14 µmol/L depressed Zn binding plus uptake (Hansen et al, 1996). Because CPP can be formed in vitro by pepsin digestion of casein (Berrocal et al, 1989), the decrease in Zn uptake found in the present assays may also be due to the presence of similar compounds.…”
Section: Table 3 Body Weight Increase and Food Efficiency In Rats Fementioning
confidence: 49%
“…Assays with Caco-2 cells have shown that the addition of certain casein phosphopeptides (CPP-Ca) at levels higher than 14 µmol/L depressed Zn binding plus uptake (Hansen et al, 1996). Because CPP can be formed in vitro by pepsin digestion of casein (Berrocal et al, 1989), the decrease in Zn uptake found in the present assays may also be due to the presence of similar compounds.…”
Section: Table 3 Body Weight Increase and Food Efficiency In Rats Fementioning
confidence: 49%
“…Milk and dairy products provide plenty of Ca 2+ , which can form soluble complexes with those phosphopeptides, thus avoiding Ca phosphate precipitation (Sato, Naguchi, & Naito, 1986;Berrocal et al, 1989), and enhancing intestinal absorption of Ca and retention thereof in the body (Mykk. anen & Wasserman, 1980;Sato et al, 1986).…”
Section: Article In Pressmentioning
confidence: 99%
“…Les différents récepteurs caséini-ques étudiés étaient les caséines totales (Harzer et Kauer, 1982), les caséines individuelles (Brulé et Fauquant, 1982;Baumy et al, 1989) et les CPP (Brulé et al, 1980;Berrocal et al, 1989). Il ressort de ces études que la capacité ainsi que l'affinité des CPP pour les cations dépendent à la fois du degré de phosphorylation des caséines (as > 13 > K) et du cation utilisé (Demott et Dincer, 1976;Lonnerdal et al, 1985).…”
Section: La Présenceunclassified